The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/irv.12842
|View full text |Cite
|
Sign up to set email alerts
|

Comparative incidence and burden of respiratory viruses associated with hospitalization in adults in New York City

Abstract: Background Although the burden of influenza is well characterized, the burden of community‐onset non‐influenza respiratory viruses has not been systematically assessed. Understanding the severity and seasonality of non‐influenza viruses, including human coronaviruses, will provide a better understanding of the overall disease burden from respiratory viruses that could better inform resource utilization for hospitals and highlight the value of preventative strategies, including vaccines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Other authors have noted similar findings when comparing RSV and influenza hospitalizations [ 10 , 23 , 24 ]. Tseng et al (2020) reported high levels of MRU for RSV patients during hospitalization, with 21.4% of patients requiring ventilation support and 17.9% admitted to the ICU, as well as hospital readmissions within the first 30 days postdischarge exceeding 15% and substantial health care services utilization postdischarge [ 25 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Other authors have noted similar findings when comparing RSV and influenza hospitalizations [ 10 , 23 , 24 ]. Tseng et al (2020) reported high levels of MRU for RSV patients during hospitalization, with 21.4% of patients requiring ventilation support and 17.9% admitted to the ICU, as well as hospital readmissions within the first 30 days postdischarge exceeding 15% and substantial health care services utilization postdischarge [ 25 ].…”
Section: Discussionsupporting
confidence: 72%
“…In Bruyndonckx et al (2020), the odds of having unresolved symptoms after 28 days and illness deterioration were significantly associated with age in RSV patients but not in influenza patients [ 16 ]. Furthermore, Sieling et al (2021) found that RSV and hMPV were both associated with a longer median LOS (4.4 and 4.8 days, respectively) compared with influenza (3.9 days), with higher crude mortality [ 24 ]. In the current study, hMPV infections presented similar trends toward higher MRU compared with influenza.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Another retrospective claims study found that, among hospitalized adults in New York City, patients with RSV required a longer hospital LoS than patients with influenza (median: 4.4 vs. 3.9 days, respectively). 28 Patients with RSV also more frequently experienced acute exacerbation of asthma or COPD, exacerbation of CHF, and hypoxemia; this may parallel the association between RSV infections early in life and development of bronchospastic diseases such as asthma and recurrent wheezing in childhood. 29 , 30 …”
Section: Discussionmentioning
confidence: 91%
“…The articles from Tseng et al 36 and Sieling et al 37 were not included as they reported the same data as in Ackerson et al 20 and Branche et al, 23 respectively. More detailed characteristics of included studies are summarized in Table S2.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%